Some Noncommutative Matrix Algebras Arising in the Bispectral Problem - Grünbaum, F.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
I revisit the so called ''bispectral problem'' introduced in a joint paper with Hans Duistermaat a long time ago, allowing now for the differential operators to have matrix coefficients and for the eigenfunctions, and one of the eigenvalues, to be matrix valued too. In the last example we go beyond this and allow both eigenvalues to be matrix valued.